Approaches to improve wheat grain quality: breeding for falling number - V. A. Krupnov; O. V. Krupnova (Вавиловский журнал генетики и селекции)
Falling number (FN) reflects the level of alpha amylase activity in grain. The main factor responsible for high α amylase levels and low FN values is visible or hidden preharvest sprouting (PHS) under adverse weather conditions. In recent decades, great progress has been made in the understanding of biochemical and molecular processes accompanying PHS and the genetic control of preharvest sprouting resistance (PHSR) and FN, as well as in the development of methods of breeding for PHSR and FN. However, breeding for these traits and the corresponding theoretical studies have not yet been properly developed or reflected in the Russian literature. The purpose of the review is to fill this gap. It illustrates the genetic complexity and context dependence of the PHSR and FN traits and of major factors impairing FN. A specific feature of breeding for high PHSR and FN is that it involves elimination of late maturity α-amylase (LMA) genotypes in choosing parents for crossing and from early hybrid generations; choice of donors of target traits with regard to their genetic diversity; methods of evaluation of varieties and lines for PHSR and FN under different environmental conditions; determination of F2 population size with regard to combination of PHSR, FN, high performance, grain quality, and other commercial traits. New methods and approaches in breeding open new prospects. They include the doubled haploid (DH) method, allowing homozygotes to be obtained from early hybrid generations; and DNA technologies, which permit genetically reasonable selection of PHSR and FN donors, pyramiding of desirable alleles, and efficient selection of desired offspring using closely linked molecular markers.